Analisis Butir Soal Ips Uts Semester Genap Pada Siswa Kelas Ix Smp Muhammadiyah 10 Surakarta Tahun Ajaran 2015/2016 - FITRIANI, DESI, Drs. Budi Sutrisno, M.Pd (2016)
Evaluation that had been carried out in SMP Muhammadiyah 10 Surakarta has not noticed an assessment of the items that have been prepared. The purpose of this study is: To determine 1) Characteristics of the difficulty level of items on the analysis of 10 SMP Muhammadiyah Surakarta academic year 2015/2016. 2) The characteristics distinguishing the analysis of items on SMP Muhammadiyah 10 Surakarta academic year 2015/2016. 3) Characteristics effectiveness analysis humbug items on SMP Muhammadiyah 10 Surakarta academic year 2015/2016. This study uses a qualitative ethnographic research design. The technique of collecting data using interviews and documentation. Data analysis techniques to measure data collection, data reduction, data presentation and conclusion. The documentation data were analyzed using the program as Anates Version 4. The results of this study indicate that for 1) Level of difficulty about IPS has a difficult category and is easily influenced by the learning material that was delivered previously by the teacher. In detail that the multiple choice questions categorized difficult 8 matter (18%), while 26 questions (58%), easy 5 questions (11%), a very easy 5 questions (11%), and a very difficult one matter (2% ). Description amounting to about 5 points matter, all included in the medium category. 2) Power problems distinguishing between IPS has been able to measure the high caliber of students with poor performance. In detail that the multiple choice questions, including different power categories negative 3 problems (7%), weak 10 questions (22%), just 15 questions (33%), both 17 questions (38%). Description amounting to about 5 points matter, which is included in the category of just 1 question (20%), both 4 questions (80%). 3) The effectiveness of IPS posing on a matter put on the multiple choice questions for a particular problem points. In detail that the multiple choice questions, including posing with a very good criteria consists of 4 questions (9%), both with 16 questions (35%), less amounts to 9 questions (20%), bad consists of 4 questions (9%), and very bad totalling 12 questions (27%).